Nutritional and Health Benefits of Millets (AYUSHDHARA, 2023)
Millets are group of small seeded grasses that have been cultivated for thousands of years in various parts of the world. They are highly nutritious and versatile, making them an essential part of many traditional diets. Millets are also drought-resistant and require less water than other cereal crops, making them an ideal crop of regions with limited water resources. There are several types of millets like Sorghum, Pearl millet, Proso millet, Kodo millet, Finger millet, Foxtail millet and Barnyard millet, Little millet, Browntop millet. Each type has its unique nutritional profile and uses. Apart from being a nutritious food source, millets also have several health benefits. They are gluten-free, making them an excellent alternative for people with celiac disease or gluten intolerance. Millets are also low in glycemic index, making them an ideal food for people with diabetes. They also have a environmental benefits as they require less water than other crops like rice, wheat, making them ideal for regions with limited water resources. So, this article is an effort to put emphasis on Nutritional and Health Benefits of millets.